How do the Black Hole and the Universe Form? - Yin, Mei (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to attempt to clarify how the black hole and the universe form by finding root causes of formations of the black hole and the universe and put forward a new theoretical point of view based on related physical and chemical theories. When the black hole exploded under incredibly high temperatures, all liquid and solid substances exploding out of the black hole have been in gaseous phase besides original gases. Generally speaking, the farthest away from the sources of heat the gases arrive, the fastest they become cool. Adjacent gases gradually mass and form a gaseous lump under inter-atom gravitations between them when they cool down. When they become cooler and colder to a sufficiently low temperature, they will gradually form a star- or planet-like object. Similar cases happen to other stars, planets, asteroids, smaller objects, etc. The universe was born. When sources of heat (e.g., the Sun) burn themselves out sometime in the future, e.g., in several billions of years, they will no longer release heat and gradually cool down. With mutual attraction of stars and planets under atomic gravitations between them, colder and contracting stars and planets gradually move nearer one another, finally connect one another and gel altogether on the basis of the principle of expanding when heated and contracting when cooled in general cases. As the stars and planets become much colder, they will further fuse together and remarkably contract and gradually become a small object, which looks perhaps like a small eddy from afar, or a black hole.